Rapid Administration of High-Dose Intravenous Methylprednisolone Improves Visual Outcomes After Optic Neuritis in Patients With AQP4-IgG-Positive NMOSD - Akaishi, Tetsuya; Takeshita, Takayuki; Himori, Noriko; Takahashi, Toshiyuki; Misu, Tatsuro; Ogawa, Ryo; Kaneko, Kimihiko; Fujimori, Juichi; Abe, Michiaki; Ishii, Tadashi; Fujihara, Kazuo; Aoki, Masashi; et al. (Frontiers in Neurology, 2020)
Objective: The purpose of this study was to elucidate the rapid impact of high-dose intravenous methylprednisolone pulse therapy (1,000 mg/day for 3 days) on the eventual visual prognosis in patients with serum anti-aquaporin-4 immunoglobulin G (AQP4-IgG)-positive neuromyelitis optica spectrum disorders (NMOSD) who had an attack of optic neuritis (ON). Methods: Data from 32 consecutive NMOSD patients (1 male and 31 female) with at least one ON attack, involving a total of 36 ON-involved eyes, were evaluated. The following variables at ON onset were evaluated: sex, age at the first ON episode, visual acuity at nadir, visual acuity after 1 year, duration from ON onset to treatment for an acute ON attack, cycles of high-dose intravenous methylprednisolone pulse therapy for the ON attack, and cycles of plasmapheresis for the ON attack. Among the 36 ON-involved eyes, 27 eyes were studied using orbital magnetic resonance imaging (MRI) with a short-T1 inversion recovery (STIR) sequence and gadolinium-enhanced fat-suppressed T1 imaging before starting treatment in the acute phase. Results: In univariate analyses, a shorter duration from ON-onset to the initiation of high-dose intravenous methylprednisolone pulse therapy favorably affected the eventual visual prognosis 1 year later (Spearman’s rho = 0.50, p = 0.0018). The lesion length on orbital MRI was also correlated with the eventual visual prognosis (rho = 0.68, p < 0.0001). Meanwhile, the days to steroid pulse therapy and lesion length on orbital MRI did not show a significant correlation. These findings suggest that the rapidness of steroid pulse therapy administration affects the eventual visual prognosis independent of the severity of ON. In multivariate analysis, a shorter time from ON onset to the start of acute treatment (p = 0.0004) and a younger age at onset (p = 0.0071) were significantly associated with better visual outcomes. Conclusions: Rapid initiation of high-dose intravenous methylprednisolone pulse therapy is essential to preserve the eventual visual acuity in patients with serum AQP4-IgG-positive NMOSD. Once clinicians suspect acute ON with serum AQP4-IgG, swift administration of steroid pulse therapy before confirming the positivity of serum AQP4-IgG would be beneficial for preserving visual function.